Resveratrol Relaxes Human Gastric Smooth Muscles Through High Conductance Calcium-Activated Potassium Channel in a Nitric Oxide-independent Manner - Modzelewska, Beata; Drygalski, Krzysztof; Hady, Hady Razak; Kiełczewska, Aleksandra; Chomentowski, Andrzej; Koryciński, Krzysztof; Głuszyńska, Paulina; Kleszczewski, Tomasz (Frontiers in Pharmacology, 2022)
Resveratrol, as a polyphenolic compound that can be isolated from plants, and also a component of red wine has broad beneficial pharmacological properties. The aim was to investigate the role of nitric oxide and potassium channels in resveratrol-induced relaxation of human gastric smooth muscle. Gastric tissues were obtained from patients who underwent sleeve gastrectomy for severe obesity (n=10 aged 21-48; BMI 48.21±1.14). The mechanical activity from the muscle strips was detected under isometric conditions as the response to increasing concentrations of resveratrol before and after different pharmacological treatments. Resveratrol caused an observable, dose-dependent gastric muscle relaxation. The maximal response caused by the highest concentration of resveratrol was 83.49±2.85% (p<0.0001) of the control. Preincubation with L-NNA, L-NAME, or ODQ did not prevent the resveratrol-induced relaxation. Apamin, glibenclamide, 4AP or tamoxifen, did not inhibit the relaxing effect of resveratrol, as well. In turn, blocking BKCa by TEA, iberiotoxin, or charybdotoxin resulted in inhibition of resveratrol-induced relaxation (91.08±2.07, p<0.05; 95.60±1.52, p<0.01 and 89.58±1.98, p<0.05, respectively). This study provides the first observation that the relaxant effects of resveratrol in human gastric muscle strips occur directly through BKCa channels and independently of nitric oxide signaling pathways. Furthermore, there is considerable potential for further extensive clinical studies with resveratrol as an effective new drug or health supplement to treat gastrointestinal dyspepsia and other gastric hypermotility disorders.